A comparative study of graphene growth on SiC by hydrogen-CVD or Si sublimation through thermodynamic simulations. Issue 26 (8th June 2018) - Dagher, Roy; Blanquet, Elisabeth; Chatillon, Christian; Journot, Timotée; Portail, Marc; Nguyen, Luan; Cordier, Yvon; Michon, Adrien
Abstract : Thermodynamic simulations of SiC hydrogen annealing illustrating the impossibility of graphene formation due to the high pressure of C–H gases. Abstract : Chemical vapor deposition (CVD) with hydrogen is an interesting technique to grow graphene on silicon carbide (SiC) with excellent electronic properties. However, unanswered questions remain concerning whether the growth mechanism is similar or different to the graphene growth by silicon (Si) sublimation from SiC. In this paper, we emphasize the differences between these two methods based on thermodynamic simulations in an attempt to better understand the different contributors to the graphene formation in both cases. Our calculations prove that our growth technique, i.e. CVD with hydrogen, operates in a completely different thermodynamic system compared to the Si sublimation technique due to the presence of hydrogen. Finally, we complete our simulations with experimental graphene growth attempts which confirm the necessity of an external carbon source to grow graphene under a hydrogen atmosphere in a CVD reactor, unlike the Si sublimation technique.